Synthesis and Spectroscopic Studies of Some Metal Complexes of [3-(3-(2-chloroacetyl)thioureido)pyrazine-2-carboxylic acid] - M . Sarhan, Basima (Al-Qadisiyah Journal of Pure Science, 2018)
A new ligand [3(3(2chloroacetyl) thioureido)pyrazine-2-carboxyliIcacid](CPC)was synthesized by reaction of rized by imicro elmental analysis C.H.N.S.,FT-IR,UV-Vis and 1H-13CNMR spectra, some transition metals complex ofIthis ligand were Prepared and characterized byiFT-IR,UV-Vis spectra conductivity measurements magnetic susceptibility and atomic absorption. From the obtained results the molecular formula of all prepared complexes were[M(CPC)2](M+2i=Mn. Co, Ni, Cu, Zn, Cd and Hg),the proposedi geometrical structure for all complexes were as tetrahedral geometry except copper complex has square planer geometry.